Explaining Clustered Ventilation Defects Via a Minimal Number of Airway Closure Locations - Mullally, William (2008)
Computational models of the human lung have been developed to study lung physiology and have been used to identify the airways responsible for mechanical dysfunction in asthmatics. Tgavalekos et al. used models anatomically consistent with the human lung to link ventilation defects to the heterogeneous closure of small airways. Their approach implicitly assumed a high degree of independence between airway closures as indicated by the low compactness of the airway structures mapped to individual ventilation defects. Venegas et al. however, have found that significant mutual dependence of airways may play a role in patchy ventilation of asthmatics. This led us to explore the question to what extent anatomically consistent models can be built which do not implicitly assume high independence of airways but instead allow for the mutual dependence of airways responsible for ventilation defects. We propose an algorithm for generating subject-specific airway-tree models that minimize the number of airways that must be closed or severely constricted to cause observed ventilation defects. We also propose novel approaches for measuring the compactness of airway structures. Our approach shows that anatomically consistent models which link compact airway structures to ventilation defects can be built. Our model also shows that some ventilation defects may be caused by closures of larger airways than previously reported.